1995
DOI: 10.1016/0014-5793(95)00149-4
|View full text |Cite
|
Sign up to set email alerts
|

ω‐agatoxin IVA blocks nicotinic receptor channels in bovine chromaffin cells

Abstract: We have studied the contribution of P-type voltagedependent Ca 2+ channels to both catacholamine (CA) and ATP secretion from bovine chromaffin cells induced by high K ÷ or nicotine using ¢o-agatoxin IVA, a selective blocker of P-type voltage-dependent Ca 2÷ channels. We found that high K ÷ (75 raM) induced the release of about 13% of norepinephrine, 5% epinephrine and 11% ATP, and that ¢o-agatoxin (100 nM) did not affect this secretion. However, both nicotine-induced CA and ATP secretion were significantly blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Recording of chromaffin cell nicotinic receptor‐activated currents under voltage‐clamp was done, using the nystatin‐perforated patch‐clamp technique, as previously described [14]. Chromaffin cells were bathed in a solution with the following ionic composition (in mmol/l): NaCl 140; KCl 5.9; MgSO 4 1.2; CaCl 2 2.5; HEPES 15 and glucose 11 (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Recording of chromaffin cell nicotinic receptor‐activated currents under voltage‐clamp was done, using the nystatin‐perforated patch‐clamp technique, as previously described [14]. Chromaffin cells were bathed in a solution with the following ionic composition (in mmol/l): NaCl 140; KCl 5.9; MgSO 4 1.2; CaCl 2 2.5; HEPES 15 and glucose 11 (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Granja et al (180) showed that catecholamine secretion induced by high K ϩ is not affected by -agatoxin IVA (100 nM); nevertheless, when secretion was activated by nicotine, the -agatoxin significantly decreased catecholamine release by 50%. Thus Granja et al (180) conclude that -agatoxin IVA could also affect the nicotinic receptor.…”
Section: B Bovine Chromaffin Cellsmentioning
confidence: 97%
“…Granja et al (180) showed that catecholamine secretion induced by high K ϩ is not affected by -agatoxin IVA (100 nM); nevertheless, when secretion was activated by nicotine, the -agatoxin significantly decreased catecholamine release by 50%. Thus Granja et al (180) conclude that -agatoxin IVA could also affect the nicotinic receptor. Duarte et al (129) show that FTX decreases K ϩ -evoked norepinephrine release to 25% and epinephrine release to 39% of the control levels; the combination of FTX plus nitrendipine further decreases norepinephrine and epinephrine release to 12 and 24% of the control levels.…”
Section: B Bovine Chromaffin Cellsmentioning
confidence: 97%
“…Catecholamine secretion induced by K + depolarisation has been shown to be 20-50% dependent upon entry of calcium through L-type calcium channels (Lopez et al 1993(Lopez et al , 1994. K + -induced secretion from bovine chromaffin cells does not require entry of calcium through N- (Owen et al 1989) or P-type (Granja et al 1995) calcium channels but ω-conotoxin MVIIC reduces secretion by 50%. In preliminary experiments, we have found K + -induced secretion was reduced by nitrendipine, ω-agatoxin IVA and by ω-conotoxin MVIIC, but not by ω-conotoxin GVIA (O'Farrell and Marley, unpublished).…”
Section: The Role Of Calcium Channels In Secretionmentioning
confidence: 99%
“…The contribution of different types of calcium channels to calcium-dependent secretion induced by nicotinic receptor agonists are inconclusive due to the ability of calcium channel antagonists to block the nicotinic receptor channel. Both dihydropyridines (Lopez et al 1993) and ω-agatoxin IVA (Granja et al 1995) have been shown to inhibit responses to nicotinic agonists without comparable effects on K + depolarisation, indicating that these antagonists may have an action in addition to blocking the voltage-sensitive channels.…”
Section: The Role Of Calcium Channels In Secretionmentioning
confidence: 99%